Effects of physical activity and use of digital devices on visual acuity in children and adolescents during the COVID-19 pandemic: A cross-sectional study - Zheng, Xiao; Shi, Lei; Ou, Weiyan; Xue, Yaqing; Xu, Ying; Xue, Benli; Zhang, Jiachi; Liang, Pengyan; Huang, Wei; Qin, Zuguo; Zhang, Chichen (Frontiers in Public Health, 2022)
Purpose To determine the association between poor visual acuity, the use of digital devices and physical activity (PA) during the COVID-19 pandemic. Methods A total of 327,646 Chinese children and adolescents were included in the analysis using a cluster random sampling method; this is a case-control study, of those 144,708 children and adolescents with poor visual acuity were included in the case group, while 182,938 who did not have poor visual acuity were included in the control group. A logistic regression model was used to assess the contribution of PA and the use of digital devices to poor visual acuity. Results A total of 144,708 children and adolescents experienced poor visual acuity during the COVID-19 pandemic; 54.8% were male, and 55.2% live in rural areas. Compared to controls, children and adolescents with poor visual acuity exhibited more time for the use of digital devices (4.51 ± 2.44 vs. 3.79 ± 2.34 for cases and controls, respectively; P < 0.001) and PA (3.07 ± 0.92 vs. 2.85 ± 1.00 for cases and controls, respectively; P < 0.001). During the COVID-19 pandemic, risk factors related to poor visual acuity among children and adolescents included the use of digital devices (OR 1.135; 95% CI 1.132–1.139), and PA (OR 1.269; 95%CI 1.259–1.278). The results of interaction analysis show that for children and adolescents aged 12 to 17, the positive association between the use of digital devices and poor visual acuity decreased. The interaction effect between PA and digital devices is 0.987. Conclusions Children and adolescents were at risk of poor visual acuity during the COVID-19 pandemic. Extended use of the digital devices increased the risk of poor visual acuity, especially for children aged 6–11 years. But the risk of poor visual acuity among children and adolescents decreases as the time spent on PA increases.